Strength of a feldspar ceramic according to the thickness and polymerization mode of the resin cement coating - Salazar Marocho, Susana Maria [UNESP]; de Melo, Renata Marques [UNESP]; Scavone Macedo, Luis Guilherme [UNESP]; Valandro, Luiz Felipe; Bottino, Marco Antonio [UNESP] (Japanese Soc Dental Materials Devices, 2011)
The aim of this study was to evaluate, in vitro, the biaxial flexural strength (ISO 6872) of a feldspathic ceramic (VM7, Vita Zahnfabrik) coated with a resin cement with different thicknesses and polymerization mode. Control groups consisted in VM7 with and without acid etching with 10% hydrofluoric acid for 1 min. Experimental groups comprised VM7 etched, silanated and coated with Variolink (Ivoclar Vivadent) cement, that was polymerized through the porcelain in light-cure and dual-cure modes, with thickness <= 150 mu m or > 150 mu m. The specimens (n=15) were subjected to the biaxial flexural strength essay and analyzed fractographically. Parametric (Dunnet, Anova 2-way, Tukey) and non-parametric tests (Weibull) were used to evaluate results. Ceramic disks coated with resin cements of either activation modes and thicknesses exhibited higher flexural strength while the Weibull moduli did not present significant differences for a confidence interval of 95%.
Keywords: Dental porcelain; Resin cement; Flexural strength; Weibull modulus